Screening for latent tuberculosis infection by an Aboriginal Community Controlled Health Service, New South Wales, Australia, 2015 - Hannah Visser; Megan Passey; Emma Walke; Sue Devlin (World Health Organization Regional Office for the Western Pacific, 2020)
Objective: Ongoing transmission of tuberculosis (TB) continues in Indigenous communities in New South Wales (NSW), Australia. In a pilot project, a Public Health Unit TB team partnered with an Aboriginal Community Controlled Health Service (ACCHS) in a community with a cluster of TB to augment screening for latent TB infection (LTBI) using interferon-gamma release assay (IGRA). This study examined screening data and programme outcomes at 12 months post hoc to advise practice and policy formulation. Methods: We conducted a retrospective, cross-sectional analysis of demographic and clinical data of ACCHS patients, stratified by IGRA testing status. Differences in sex and age distribution between the groups and cases of a genetically and epidemiologically linked TB cluster in Aboriginal people in NSW were assessed using non-parametric tests. Results: Of 2019 Aboriginal and Torres Strait Islander people seen by general practitioners during the study period, 135 (6.7%) participated in the screening. Twenty-four (17.8%) participants were IGRA positive. One person was diagnosed with active TB. Twelve participants received a chest X-ray at the time of the positive test, and six participants had an additional chest X-ray within 12 months. None commenced preventive treatment for LTBI. Discussion: ACCHS screening for LTBI reached individuals in the age group most commonly affected by TB in these Aboriginal communities. No conclusions can be made regarding the population prevalence due to the low screening rate. Further strategies need to be developed to increase appropriate follow-up and preventive treatment.